2012
DOI: 10.1007/s11999-011-2096-3
|View full text |Cite
|
Sign up to set email alerts
|

Bony Impingement Limits Design-related Increases in Hip Range of Motion

Abstract: Background Factors affecting risk for impingement and dislocation can be related to the patient, implant design, or surgeon. While these have been studied independently, the impact of each factor relative to the others is not known. Questions/purposes We determined the effect of three implant design factors, prosthetic placement, and patient anatomy on subject-specific ROM. Methods We virtually implanted hip geometry obtained from 16 CT scans using computer models of hip components with differences in head siz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 42 publications
0
19
0
Order By: Relevance
“…Models using the angle at prosthetic impingement as a marker for risk of dislocation reported increased hip range with larger head sizes primarily because of the increase in head–neck ratio . Conversely, when bony impingement is also simulated, we and others found that head size >32 mm did little to improve range of motion before impingement, especially when components were placed within the optimum range …”
mentioning
confidence: 54%
See 2 more Smart Citations
“…Models using the angle at prosthetic impingement as a marker for risk of dislocation reported increased hip range with larger head sizes primarily because of the increase in head–neck ratio . Conversely, when bony impingement is also simulated, we and others found that head size >32 mm did little to improve range of motion before impingement, especially when components were placed within the optimum range …”
mentioning
confidence: 54%
“…CAD models of THA components (Secur‐Fit HA) were provided by Stryker Orthopaedics (Mahwah, NJ) in four head diameters (28, 32, 36, and 44 mm) and were combined with a femoral component with a neck diameter of 12.5 mm and neck‐stem angle of 132°. These components were aligned to the geometry of each hip using a previously described technique . We chose an orthogonal coordinate system based on the recommendation of the International Society of Biomechanics and oriented the pelvis so that the anteroposterior iliac spines were level and in the same frontal plane as the pubic symphysis (no lordosis or pelvic obliquity).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In these patients, we hypothesize that the instability caused anteroinferior abrasion of the cartilage with rupture and degeneration of the labrum, similar to a posteroinferior contre-coup lesion that can be seen with anterior pincer impingement [2]. Extraarticular impingement has been described in the arthroplasty literature [5,14], and there are a few case reports of ischiofemoral impingement, although primarily from the lesser trochanter rather than from the greater trochanter [1,26,37]. Extraarticular impingement has also been recognized in the context of Legg-Calvé-Perthes deformity, where the relative overgrowth of the greater trochanter impinges on the iliac wing when the hip is abducted [8].…”
Section: Discussionmentioning
confidence: 99%
“…Impingement and instability can, however, occur circumferentially around the acetabular rim [2,11] and can also be initiated extraarticularly, causing secondary intraarticular damage [5,9,14]. The cause of more unusual patterns of FAI is multifactorial and results from a combination of Each author certifies that he or she, or a member of his or her immediate family, has no commercial associations (eg, consultancies, stock ownership, equity interest, patent/licensing arrangements, etc) that might pose a conflict of interest in connection with the submitted article.…”
Section: Introductionmentioning
confidence: 99%